Bisphenol A Exposure and its Impact on Multi-System Pathological Changes in Laboratory Animal Models - A Review - Siva, S,; N. Pazhanivel,; S. Vairamuthu,; L. Kalaiselvi,; Biswadeep Behra, (The Indian Veterinary Journal, 2024)
Bisphenol A (BPA), a synthetic compound found in polycarbonate plastic widely used in food and drink packaging, medical devices, thermal paper, and dental materials, presents health risks due to contamination in various sources. Due to its mass productions and widespread applications, the presence of BPA is ubiquitous in the environment. It accumulates in human tissues, exhibiting hormone-like properties by binding to estrogen receptors, affecting body weight, and influencing carcinogenesis. BPA interacts with GPR30, impacting metabolism and cancer progression, and may disrupt male reproductive function through androgen receptor binding. Key transcription factors, including PPARγ, C/EBP, Nrf2, HOX, and HAND2, contribute to BPA's effects on fat, liver, cardiovascular health, and cancer. Additionally, epigenetic changes such as DNA methylation, histone modification, and altered microRNA expression contribute to the pathological effects of BPA. Research studies using in vitro cell lines, rodent models, and epidemiological analysis have convincingly shown the increasing susceptibility to cancer at doses below the oral reference dose set by the Environmental Protection Agency for BPA. The purpose of this review is to analyze the mechanism of action of bisphenol A, with a special focus on multi systemic pathological changes in animal models.